Increased Twist and ZEB2 expression in a cutaneous metastasis of high‐grade glioma. Issue 2 (21st December 2019) - Nagaishi, Masaya; Fujii, Yoshiko; Sugiura, Yoshiki; Takano, Issei; Takigawa, Tomoji; Yokoo, Hideaki; Suzuki, Kensuke
Abstract : Extra‐central nervous system metastasis of gliomas is extremely rare, and the biological mechanism underlying it remains poorly understood. Epithelial‐to‐mesenchymal transition (EMT) has received attention as one of the important processes of cancer metastasis. Here we describe the case of a 32‐year‐old man with cutaneous metastasis of high‐grade glioma, together with the analysis of EMT‐related molecules. Our patient presented with a high‐grade glioma in the right frontal lobe. Cutaneous metastasis under the surgical scar developed 17 months after complete resection of the intracranial tumor. Histopathology of both the original and metastatic tumors revealed hypercellularity; the tumors predominantly comprised glial tumor cells with poor cellular processes. Immunohistochemical analysis demonstrated intense expression of nestin, focal expression of glial fibrillary acid protein, and absence of expression of oligodendrocyte transcription factor 2, endothelial membrane antigen, or neurofilament. Genetic analyses could not provide definitive diagnostic information of glioma subtypes. Immunohistochemical analysis for EMT‐related biomarkers demonstrated increased Twist, zinc finger E‐box‐binding homeobox 2 (ZEB2), matrix metalloproteinase 2 (MMP2), and MMP9 expressions in tumor cells of the metastatic lesion compared with those of the primary lesion. Slug, E‐cadherin, and N‐cadherin expression were absent in both primary and metastatic lesions; however, ZEB1 expression was present in both. Our results suggest that Twist, ZEB2, MMP2, and MMP9 facilitate cutaneous metastasis of gliomas.